Effect of recycling process in twin screws extruder HAAK on structure and crystallization behavior of polypropylene - Chuong, Bui; Villoutreix, Gilbert; Phuong, Nguyen Tri (Vietnam Journal of Chemistry, 2014)
Recycling process of polypropylene (PP) in twin screws extruder HAAK at high (195 - 230oC) and low (175-190oC) temperature ranges was studied. IR spectra and solubility of recycled samples show that neither oxidative degradation nor network formation has occurred at recycling conditions. So only degradation of PP molecules to smaller fractions may take place, that contributes to increasing of Melt Flow Index (MFI) of recycled samples. The results show also the stronger effect of recycling temperatures on the structure changes than that of number of recycling times. We can see also the structure changes of recycled PP cause the higher crystallization rate, higher crystalline percentage of spherulite formations with smaller dimensions. It leads to higher crystallization temperatures (3-4oC) but lower melting temperatures (4-5oC) of recycled PP in comparison with virgin PP.